MANAJEMEN RISIKO KEAMANAN ASET TEKNOLOGI INFORMASI MENGGUNAKAN ISO 31000:2018 DISKOMINFO KOTA SALATIGA - Muhammad Ilham Fachrezi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The Office of Communication and Information Technology (DISKOMINFO) Salatiga City is a government agency that uses information technology as an important role to support business processes. For this reason, it is necessary to have risk management as a standard or guide in the handling and protection of information technology assets. The purpose of this study is to identify, analyze and manage the security risks of information technology assets and also to determine the level of risk in the security aspects of information technology assets. The application of risk management in this study uses ISO 31000: 2018 which consists of the risk identification stage, the risk analysis stage, the risk evaluation stage, and the risk treatment stage. From the results of this study, there are 2 possible low-level risks, 11 medium-level possible risks, and 4 high-level risks. From these results, DISKOMINFO Salatiga City requires special attention to the problems of frequent power outages, servers down, internet connection that often breaks, and lightning strikes.